More destructive than guns: contagious epidemic fever and public health in Lisbon, 1810-1812 - Cabral de Freitas Ricardo (SHS Web of Conferences, 2022)
The paper analyzes the controversy on the contagious epidemic fever in Lisbon between 1810 and 1811. Occurred during the last French invasion in Portugal, the epidemic was caused, among other factors, by the intense migratory flow of refugees displaced to the capital from countryside villages. Faced with the spread of the disease, the health services of Lisbon put in place preventive measures to curb its reach and disseminated preventive guidelines to the population. However, after French retreat in the early spring of 1811, the status of the epidemic itself, as well as the legitimacy of the measures taken, would be the subject of intense dispute. We propose an analysis of the controversy between Henrique Xavier Baeta, a navy physician who reported the events in the Memória sobre a febre epidêmica contagiosa (1812), and the editors of Jornal de Coimbra, who published a critical examination of Baeta’s book. For the latter, the main disease in those months would have been dysentery rather than fever, and its extent, much smaller than that reported by Baeta. The paper aims to show how different conceptions of disease and health underpinned both sides of the debate that spanned months in local newspapers. The analysis focuses on three of the main axes of the dispute: the effectiveness of the quarantine methods applied, the dispute over the most appropriate fumigation techniques, and the ability of Lisbon's public health services to respond to the crisis.